2020
DOI: 10.21203/rs.3.rs-40198/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Multi-Antigenic SARS-CoV-2 Vaccine Using a Synthetic Poxvirus Platform

Abstract: Modified Vaccinia Ankara (MVA) is a highly attenuated poxvirus vector that is widely used to develop vaccines for infectious diseases and cancer. We developed a novel vaccine platform based on a unique three-plasmid system to efficiently generate recombinant MVA vectors from chemically synthesized DNA. In response to the ongoing global pandemic caused by SARS coronavirus-2 (SARS-CoV-2), we used this novel vaccine platform to rapidly produce fully synthetic MVA (sMVA) vectors co-expressing SARS-CoV-2 spike and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Due to their relatively high recombination rates, the availability of simple recombinant virus construction procedures, the lack of integration into the host genome, and their ability to incorporate >25 kb of foreign DNA, poxviruses are being actively pursued as vectors for gene therapy and for applications in oncolytic virotherapy [8][9][10]. In addition, because poxvirus vectors can stimulate strong humoral and T cell-mediated responses to heterologous antigens, poxviruses are also being applied to the development of vaccines for the treatment of other infectious diseases [11][12][13]. These reasons and the ability of poxviruses to manipulate a wide-range of host processes have made studies of these viruses invaluable in understanding host-pathogen interactions and human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their relatively high recombination rates, the availability of simple recombinant virus construction procedures, the lack of integration into the host genome, and their ability to incorporate >25 kb of foreign DNA, poxviruses are being actively pursued as vectors for gene therapy and for applications in oncolytic virotherapy [8][9][10]. In addition, because poxvirus vectors can stimulate strong humoral and T cell-mediated responses to heterologous antigens, poxviruses are also being applied to the development of vaccines for the treatment of other infectious diseases [11][12][13]. These reasons and the ability of poxviruses to manipulate a wide-range of host processes have made studies of these viruses invaluable in understanding host-pathogen interactions and human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Plentiful studies target arboviruses that are on the rise: dengue virus [161], Zika virus [50,[162][163][164][165], West Nile virus [166], yellow fever virus [167], tick-borne encephalitis virus [168,169], chikungunya virus [163,170], and Crimean-Congo hemorrhagic fever virus [171]. Multiple diseases of high prevalence or fatality rate, especially those with epidemic or pandemic potential garner particular attention, including the following examples: ebolavirus [172][173][174][175], Nipah virus [176], influenza virus [177][178][179][180], respiratory syncytial virus [181,182], Middle East respiratory syndrome coronavirus [183,184], and needless to say, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [158,[185][186][187][188][189][190][191][192][193][194][195]. Several VACV-vectored vaccines have entered clinical trials: HIV-1 [196], tuberculosis [197,198], respiratory syncytial virus [199], influenza A virus…”
Section: Other Aspects Of Innovationmentioning
confidence: 99%
“…Four out of ten of the VV-based SARS-CoV-2 vaccines that are in Phase III trials are based on NRVV platforms and all use adenoviral vectors [ 48 , 50 , 51 , 192 ]. Other vectors that are in Phase I and preclinical evaluation are gorilla adenovirus, Sendai virus vector, adeno-associated virus vector, modified vaccinia virus Ankara, parainfluenza virus 5, deactivated rabies virus and influenza A virus H1N1 vectors [ 8 , [193] , [194] , [195] , [196] , [197] ]. Replicating viral vector (RVV) Multiple SARS-CoV-2 vaccines are also being developed with attenuated viral vectors that can replicate at the site of immunization and can thus elicit stronger immune responses using relatively small vaccine doses.…”
Section: Vaccine Platformsmentioning
confidence: 99%
“…Encouragingly, the grade 3 AEs resolved without any medical intervention within 3–4 days of vaccination. None of the study participants reported any serious AEs within 28 days [ 193 ].…”
Section: Sars-cov-2 Vaccine Candidates In Phase III Clinical Trialsmentioning
confidence: 99%